The effect of π-Conjugation on the self-assembly of micelles and controlled cargo release. Issue 1 (1st January 2020) - Liang, Yan; Sun, Yalin; Fu, Xiaoheng; Lin, Yang; Meng, Zhu; Meng, Yanan; Niu, Jiping; Lai, Yusi; Sun, Yong
Abstract: Here we presented a novel micelle self-assembled from amphiphiles with π-conjugated moieties (OEG-DPH). The π-conjugated structural integrity of the micelles enabled stable encapsulation of Nile Red (NR, model drug). The self-assembly behaviour of the amphiphiles and the release profile of NR loaded micelles were investigated. Spherical core-shell structured NR loaded micelles with low CMC of 57 μg/mL and the efficient intracellular delivery process was monitored. This research provided a way to fabricate stable polymeric micelles and develop a practical nanocarrier for therapeutics delivery.